The impact of visual fidelity on screen-based virtual reality food choices: A randomized pilot study - Bianca Curi Braga; Pejman Sajjadi; Mahda Bagher; Alexander Klippel; Jessica Menold; Travis Masterson (PLoS ONE, 2025)
Objective To understand the impact of fidelity and perceived realism on virtual reality food choices, and task motivation, engagement, and interest. Design Randomized controlled trial. Setting Online. Participants 84 participants recruited from Amazon Mechanical Turk. Intervention Participants were randomly assigned to either a high- (n = 43) or a low- (n = 41) visual fidelity environment and were asked to select foods to have a meal with a friend. Main outcome measures Food choice, motivation of food choices, engagement, and interest. Analysis Simple linear regressions between visual fidelity and perceived realism, and log-linear regressions for visual fidelity or perceived realism on either motivation, interest, or engagement. Poisson models between visual fidelity or perceived realism, and food selections. Results Manipulating visual fidelity was not associated with perceived realism, motivation, interest, or engagement in the food selection task. Perceived realism increased motivation by 0.3% (SE 0.056; p = 0.022), interest by 1.4% (SE 0.002; p<0.001), and engagement by 0.9% (SE 0.001; p<0.001) in the food selection task. High visual fidelity decreased the total number of foods selected (B = 0.216; CI (-0.384; -0.047); p = 0.012). Conclusion and implications Perceived realism, but not visual fidelity, is important for task related factors like motivation, engagement, and interest. Visual fidelity may influence some food selections.